NOISE POLLUTION AND HEALTH IN NORTHERN GREATER MUMBAI: CASE OF RN WARD - Datta, Prof. Dr. Moushumi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Greater Mumbai is urbanizing at a rapid pace, leading to extensive construction activities, widespread use of machinery, and heavy traffic, which contribute significantly to noise pollution in the city. This study aims to measure noise levels in the study area, analyze their impact on residents' health, and recommend practical solutions to mitigate the adverse effects. The research methodology includes secondary data sourced from news articles to compile a literature review. Primary data is collected through a structured questionnaire administered via Google Forms to facilitate efficient data collection. A sample size of 80 respondents, randomly selected from locations with high noise levels, was chosen for the study. The key findings reveal elevated noise levels across most locations, with significant health impacts reported by respondents. These impacts include stress, sleep disturbances, and hearing impairment. The recommendations emphasize the importance of educating the public about the harmful effects of noise pollution and the need to plant large canopy trees, particularly in noisy areas, to absorb sound effectively. Additionally, hearing impairment is commonly identified as an occupational hazard, particularly among individuals working in industries associated with high noise levels.